2021
DOI: 10.1530/ec-21-0235
|View full text |Cite
|
Sign up to set email alerts
|

The association of adiponectin with risk of pre-diabetes and diabetes in different subgroups: cluster analysis of a general population in south China

Abstract: Objective: Adiponectin is an adipocyte-derived hormone with an important role in glucose metabolism. The present study explored the effect of adiponectin in diverse population groups on pre-diabetes and newly diagnosed diabetes. Methods: A total of 3300 individuals were enrolled and their data were collected in the analyses dataset from December 2018 to October 2019. Cluster analysis was conducted based on age, body mass index, waistline, body-fat, systolic blood pressure, triglycerides and glycosylated hemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…There is enough evidence to suggest that changes in adipocytokine secretion do contribute to defective insulin production/action and, concomitantly, result in peripheral insulin resistance [ 13 , 14 , 15 , 16 , 17 ]. Adipokines such as adiponectin, leptin resistin, visfatin, ghrelin and chemerin seem to play an important role in the onset, progression and complications of T2DM [ 14 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is enough evidence to suggest that changes in adipocytokine secretion do contribute to defective insulin production/action and, concomitantly, result in peripheral insulin resistance [ 13 , 14 , 15 , 16 , 17 ]. Adipokines such as adiponectin, leptin resistin, visfatin, ghrelin and chemerin seem to play an important role in the onset, progression and complications of T2DM [ 14 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Subramanian et al [ 48 ] on obese patients without severe metabolic complications, IL-10 levels have been shown to be positively correlated with the amount of white adipose tissue (WAT) [ 48 ]. Other authors have previously suggested that the measurement of serum FPG, HbA1c, HDL-C, LDL-C, VEGF and adiponectin levels may be useful in identifying the risk of obesity and/or IR [ 49 , 50 , 51 ]. Our results do not confirm previous reports by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed in tissues such as the liver, kidney, pancreas, skeletal muscle, bone, and glands [ 10 ]. It has been shown to ameliorate IR, oxidative stress, and inflammatory status using anti-diabetic, anti-oxidative, and anti-inflammatory properties for obesity-related diseases, lipid homeostasis, T2DM, and CVD [ 11 ]. The low levels of adiponectin associated with obesity-related IR, metabolic syndrome, and elevated levels of adiponectin in circulation inhibit gluconeogenic enzyme expression in T2DM mice [ 12 ].…”
Section: Introductionmentioning
confidence: 99%